Chemical constituents from the stems of Ephedra equisetina. (October 2022) - Zhu, Deng-Hui; Zhang, Jing-Ke; Jia, Ju-Fang; Liu, Juan-Juan; Wei, Jun-Jun; Yang, Meng; Yang, Ying; Li, Meng; Hao, Zhi-You; Zheng, Xiao-Ke; Feng, Wei-Sheng
Abstract: Five new compounds, including two naphthalenes (1, 2 ), a phenolic derivative (3 ) and two glycosides (4, 5 ) were isolated from the stems of Ephedra equisetina Bunge. Their chemical structures were identified by spectroscopic analyses (IR, UV, HRESIMS NMR and ECD). An in vitro bioassay suggested that compound 5 possesses potential anti-asthmatic activities. Graphical Abstract: ga1 Highlights: Five previously undescribed compounds were isolated from the stems of E. equisetina . Their structures were elucidated by NMR spectroscopy and mass spectrometry. The absolute configurations were deduced by interpretation of ECD. Anti-asthmatic effects of all of the isolated compounds were evaluated.